Aspects of Perception and Structuring of Colour Words in English and Georgian Languages - Mosiashvili, Natela; Sarajishvili, Nino ("Intercultural Dialogues" Transactions, 2025)
This study aims at a comparative exploration of the semantic structure and perception of the words denoting basic colours in two different languages, namely Georgian and English, analyzing the systems denoting colours and revealing the models of categorization of words denoting the concept of colours in order to state its relation with universal model. We have studied “colour” words in both Georgian and English Languages considering the following methods: comparative – the words in this group compare the colour or its hue to some object of the same colour; the words denoting abstract colours – these words do not reveal links with any definite object. The study of the words constituting the colour field revealed the following: analysis of the data showed that there are more colour words denoting definite colour by comparing them to the object of the same colour, in the English language more than in the Georgian language; analysis of the data revealed that the number of the words denoting abstract colours is presumably the same in the both languages. As a result of analysis of different types of relationships, a new way of structuring the lexical groups of colour were discovered implying the existence of two segments (lineal and gradual) in lexical groups of colour.